Numerical simulation of windless-air-induced added mass and damping of vibrating bridge decks. Issue 180 (September 2018) - Xu, Fuyou; Zhang, Zhanbiao
Abstract: The windless-air-induced added mass/mass moment of inertia ( m a / I a ) and damping ( c a ) effects on mechanical parameters of a vibrating bridge deck are usually ignored in wind tunnel tests. In this paper, for three typical deck sections, computational fluid dynamics simulations are carried out to study the vertical/torsional single degree-of-freedom forced vibration under windless conditions, and further to reveal the effects of m a, I a, and c a on the modal parameters. The influences of turbulence model, computational domain size, grid resolution, and time step size are analyzed. For the addressed issue, the Reynolds stress equation model (RSM) is found to be more suitable than the shear stress transportation (SST) k - ω model. A mathematical model for aerodynamic forces at zero wind speed is presented by using the dimensionless m a, I a, and c a, and they can be extracted by combining the motions and the numerically simulated aerodynamic forces using the least squares method. The numerically simulated results for an ideal plate under small amplitudes are very close to the theoretical values, and consequently verify their accuracy. The causes for the non-zero values of flutter derivatives H 4 ∗ and A 3 ∗ at zero wind speed are revealed. In the windless air, the added damping almost linearly increases with the vibration amplitude. Five existing long-span bridge deck models are taken as examples to investigate the effects of m a, I a, and c a on structural frequencies and damping ratios. Highlights: The CFD simulation is used to comprehensively study the bridge added mass and damping in windless air. Compared to SST k-w, RSM turbulence model is verified to be more appropriate for the addressed issue. The simulation accuracy is validated by using a thin plate with theoretical values. The causes for the non-zero flutter derivatives H 4 ∗ and A 3 ∗ at zero wind speed are revealed.